Pengaruh Pemberian Stigmasterol Daun Beluntas (Pluchea indica) terhadap Kerusakan Histologi Hati Tikus Putih (Rattus novergicus) Jantan sebagai Sumber Belajar Biologi - Zahidah, Ashfa; Susetyarini, Eko; Permana, Tutut Indria; Nurrohman, Endrik; Husamah, Husamah (Biocaster : Jurnal Kajian Biologi, 2025)
The implementation of a healthy lifestyle with a “back to nature” approach has become a global trend, marked by the increasing consumption of natural-based medicines which are considered relatively safer compared to synthetic drugs. The beluntas plant (Pluchea indica L.) is known to contain active compounds such as alkaloids, tannins, and flavonoids, including stigmasterol which has the potential as a pharmacological agent. This study aims to determine the effect of administering stigmasterol from beluntas leaves at various doses on liver histological damage. The study was conducted at the Biomedical Laboratory of the Faculty of Medicine, University of Muhammadiyah Malang for 28 days. The type of study used true experiment research with a RAL experimental design, consisting of four groups and six replications. The doses of each treatment were P1 (0.125 mg/kgBW), P2 (0.25 mg/kgBW), P3 (0.5 mg/kgBW), and the control group. The results of the one-way ANOVA test showed that the data on the effect of the administration of stigmasterol from beluntas leaves showed significant differences in liver cell damage in male white rats (Rattus novergicus) in parenchymatous degeneration (p = 0.010), in hydropic degeneration (p = 0.000), in karyorrhexis cells (p = 0.020), in karyolysis cells (p = 0.000), and in inflammatory cells (p = 0.021). However, the results of the one-way ANOVA test showed no significant effect on the administration of stigmasterol to pyknosis cells (p = 0.409 > 0.05). Meanwhile, the administration of stigmasterol in treatment 1 effectively reduced hydropic and prenchymatous degeneration but actually increased damage to karyolysis cells, karyorrhexis cells and inflammatory cells. This study of the effect of stigmasterol from beluntas leaves on liver histology can be used as a source of learning Biology in phase F in SMK Kesehatan class XI Pharmacology, especially in understanding drugs related to disorders of the body's system.